2014
DOI: 10.1016/j.chemosphere.2014.05.073
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection byproduct formation resulting from settled, filtered, and finished water treated by titanium dioxide photocatalysis

Abstract: This study evaluated strategies targeting disinfection byproduct (DBP) mitigation using TiO2 photocatalysis with varying influent water quality. A Purifics Photo-CAT Lab reactor was used to assess total trihalomethane (TTHM) and haloacetic acid (HAA) formation as a function of photocatalytic treatment using water from a conventional coagulation/flocculation/sedimentation process, granular activated carbon filtration, and a DBP hot spot in the water distribution system. Regardless of influent water quality, pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Due to their virucidal [ 19 , 20 ], bactericidal [ 21 , 22 ] and fungicidal [ 23 , 24 ] properties, photocatalytic layers are increasingly applied to coat surfaces in miscellaneous premises, such as farms, abattoirs, production halls, hospitals, and laboratories. The usefulness of photocatalysis has also been proven in water treatment [ 25 ], purification of drinking water [ 26 ], and air disinfection [ 27 ]. The researchers presume that the introduction of photocatalytic surfaces in the food industry, animal production, and health-care facilities will also be beneficial, as it will help prevent food poisonings and food contaminations, contribute towards the animal welfare, and improve the efficiency of pathogen eradication [ 28 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…Due to their virucidal [ 19 , 20 ], bactericidal [ 21 , 22 ] and fungicidal [ 23 , 24 ] properties, photocatalytic layers are increasingly applied to coat surfaces in miscellaneous premises, such as farms, abattoirs, production halls, hospitals, and laboratories. The usefulness of photocatalysis has also been proven in water treatment [ 25 ], purification of drinking water [ 26 ], and air disinfection [ 27 ]. The researchers presume that the introduction of photocatalytic surfaces in the food industry, animal production, and health-care facilities will also be beneficial, as it will help prevent food poisonings and food contaminations, contribute towards the animal welfare, and improve the efficiency of pathogen eradication [ 28 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…In the UV/TiO 2 photocatalysis, hydroxyl radicals ( Å OH) can enhance DOM degradation, accelerating DOM transformation to smaller molecules [36]. Complete mineralization of DOM (signified by loss of DOC), however, may only be achieved after extended treatment due to the presence and/or production of refractory compounds [25]. Therefore, these treatments usually result in changes of DOM structure and molecular characteristics.…”
Section: Dom Characteristics Before and After Treatmentmentioning
confidence: 99%
“…Mayer et al investigated disinfection byproduct (DBP) formation in TiO 2 photocatalysis with varying influent water quality. They found that photocatalysis exacerbated the production of total trihalomethane (TTHM) and haloacetic acid (HAA) beyond initial levels until economically prohibitive high energy UV lamp was used [25]. On the other hand, Wang et al found that UV irradiation could eliminate trichloromethane formation but enhanced the formation of dichloroacetic acid [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, this process may lead to the formation of various stable products that accumulate well in the solution since the total mineralization of polluted aqueous solutions is not possible with such photochemical reaction . In order to reach a high degree of mineralization of contaminated media, several Advanced Oxidation Processes (AOPs) using solar light excitation have been developed and studied in depth . They have emerged as interesting ways for an efficient decontamination of polluted media because of their large‐scale use.…”
mentioning
confidence: 99%